`That's so sexist!' How highly skilled female return migrants try to shape gender norms in Kosovo - Janine Isabelle Pinkow-Läpple (Central and Eastern European Migration Review, 2023)
Kosovo is a country profoundly shaped by migration. A growing body of literature pays tribute to this. However, up to now, it has barely focused on the implications of return. Female returnees – and especially highly skilled female returnees – are even less likely to be in the focus of research. Against this background, this paper investigates how highly skilled female Kosovars experience migration to North America or Western Europe and their subsequent return to Kosovo. Within this setup, the focus is on the impact of migration on the participants' gender norms and their attempts to shape those in Kosovo upon return. The results show that all participants experienced their sojourn abroad as empowering. The majority made use of this empowerment and actively fought for gender equality after return. However, resistance by the local population and reintegration issues impeded their engagement, prompting every second participant amongst those interviewed for this study to consider re-emigration. Despite this, two-thirds of the participants stayed and continued their engagement for gender equality but usually in an adapted manner. The paper concludes that highly skilled female return migrants have great – although fragile – potential to promote gender equality in Kosovo.
Keywords: 320; Kosovo; return migration; gender; highly skilled migrants; social remittances; intangible remittances